(untitled) - Goode, Erich (Boston, 1999)
Goode's Drugs in American Society 5/e is a well-respected, brief investigation of the full range of psychoactive drug use; from legal, medical and perscription use to criminal, recreational use and from casual use to addiction. Objective pro and con accounts on important issues like treatment, education, rehabilitation, and legalization give students a thorough understanding of the topics. The new fifth edition continues to provide the most balanced and up-to-date coverage in an accessible, engaging style.
Keywords: Drug abuse,Drug utilization; United states,United states